Measuring Mentalizing in Emotionally Focused Therapy for Couples With Childhood Sexual Abuse Survivors and Their Partners. Issue 4 (2nd October 2019) - MacIntosh, Heather B.; Fletcher, Kara; Ainsworth, Laurie
Abstract: The purpose of this study was to explore the temporal relationships between Emotionally Focused Therapy for Couples (EFT) therapist interventions and mentalizing responses in couples where one or both partners are survivors of childhood sexual abuse (CSA) by using a novel form of qualitative coding for mentalizing in EFT with CSA couples. Mentalizing can be defined as thinking about thinking. It is a developmental self-capacity that includes being able to flexibly and reflectively make sense of our internal and interpersonal mental worlds and is essential in the development and maintenance of strong interpersonal relationships. Findings of this study indicated that levels of negative mentalizing responses decreased while positive mentalizing responses increased over the course of therapy. Observed temporal relationships between therapist interventions and patient mentalizing were discussed in relation to outcomes in couple satisfaction and posttraumatic symptomatology. This novel form of coding mentalizing, while in depth, proved to be labour intensive and lacking in long-term feasibility.